Introduction to the Theme Issue on the State of the Evangelical Mind - Ream, Todd C. (Christian scholar's review, 2018)
Regardless of how one defines it, American evangelicalism is at a crossroads. The last quarter of the twentieth century was replete with signs of prosperity. Many churches, parachurch organizations, universities, and seminaries grew at unprecedented rates. Some analysts argued that the individuals populating those institutions were contributing to an intellectual renaissance.